Biosynthetic energy cost for amino acids decreases in cancer evolution. Issue 1 (December 2018) - Zhang, Hong; Wang, Yirong; Li, Jun; Chen, Han; He, Xionglei; Zhang, Huiwen; Liang, Han; Lu, Jian
Abstract Rapidly proliferating cancer cells have much higher demand for proteinogenic amino acids than normal cells. The use of amino acids in human proteomes is largely affected by their bioavailability, which is constrained by the biosynthetic energy cost in living organisms. Conceptually distinct from gene-based analyses, we introduce the energy cost per amino acid (ECPA) to quantitatively characterize the use of 20 amino acids during protein synthesis in human cells. By analyzing gene expression data from The Cancer Genome Atlas, we find that cancer cells evolve to utilize amino acids more economically by optimizing gene expression profile and ECPA shows robust prognostic power across many cancer types. We further validate this pattern in an experimental evolution of xenograft tumors. Our ECPA analysis reveals a common principle during cancer evolution. Proliferating cancer cells have a high demand for amino acids. Here, Zhang et al. show that cancer cells evolve towards gene expression profiles that use amino acids with lower biosynthetic energy costs, and demonstrate the potential prognostic utility of quantifying the extent of this adaptation.